Jugular vein vascular access ports for serial pig blood sampling in high biocontainment infectious disease studies - Layton, Rachel; Beggs, David; Mansell, Peter; Fisher, Andrew; Layton, Daniel; Boyd, Matthew; Allen, Teegan; Soldani, Elisha; Riddell, Sarah; Taylor, Grace; Williams, David T.; Stanger, Kelly J. (Frontiers in Animal Science, 2025)
Effective manual or chemical restraint of pigs for blood collection is crucial when conducting infectious disease research under high biocontainment laboratory conditions; however, these methods can introduce stress and physiological disruption. We aimed to establish proof-of-concept for the use of jugular vein vascular access ports (VAPs) for repeated, conscious blood collection in both individually and group housed pigs, trained using a positive reinforcement training regime. In study 1, pigs were housed individually, with three pigs implanted with VAPs. An additional control pig was not implanted with VAPs and was anaesthetised for all blood collections. Daily assessments of behaviour were conducted and saliva collected for corticosterone analysis. In study 2, pigs were housed in a group, with three pigs implanted with VAPs. Three control pigs were not implanted with VAPs and were anaesthetised for all blood collections. To assess the physiological impacts of both blood collection methods, heart rate variability, pulse rate and rectal temperature were assessed during a blood collection event. Across both studies 31 of 33 VAP blood collections were successful, with the remaining two collections successful using light sedation. An initial time and cost investment was required for VAP implantation, but the time required to collect blood via VAPs was halved compared to anaesthetising pigs for blood collection. One pig died during VAP surgery from anaesthesia-related complications. Pigs implanted with VAPs displayed low negative and high positive behaviour scores, low salivary corticosterone levels, and maintained steady clinical parameters during a blood collection event, whilst anaesthetised pigs displayed reduced HRV and temperature and increased pulse rate. This study provides proof-of-concept and recommendations for using VAPs in trained pigs under high biocontainment, as a welfare-positive method of conscious, repeated blood collection.